The precuneus and the insula in self-attributional processes - Cabanis, Maurice; Pyka, Martin; Mehl, Stephanie; Müller, Bernhard W.; Loos-Jankowiak, Stephanie; Winterer, Georg; Wölwer, Wolfgang; Musso, Francesco; Klingberg, Stefan; Rapp, Alexander M.; Langohr, Karin; Wiedemann, Georg; et al. (Cognitive, affective, & behavioral neuroscience, 2013)
Attributions are constantly assigned in everyday life. A well-known phenomenon is the self-serving bias: that is, people’s tendency to attribute positive events to internal causes (themselves) and negative events to external causes (other persons/circumstances). Here, we investigated the neural correlates of the cognitive processes implicated in self-serving attributions using social situations that differed in their emotional saliences. We administered an attributional bias task during fMRI scanning in a large sample of healthy subjects (n = 71). Eighty sentences describing positive or negative social situations were presented, and subjects decided via buttonpress whether the situation had been caused by themselves or by the other person involved. Comparing positive with negative sentences revealed activations of the bilateral posterior cingulate cortex (PCC). Self-attribution correlated with activation of the posterior portion of the precuneus. However, self-attributed positive versus negative sentences showed activation of the anterior portion of the precuneus, and self-attributed negative versus positive sentences demonstrated activation of the bilateral insular cortex. All significant activations were reported with a statistical threshold of p ≤ .001, uncorrected. In addition, a comparison of our fMRI task with data from the Internal, Personal and Situational Attributions Questionnaire, Revised German Version, demonstrated convergent validity. Our findings suggest that the precuneus and the PCC are involved in the evaluation of social events with particular regional specificities: The PCC is activated during emotional evaluation, the posterior precuneus during attributional evaluation, and the anterior precuneus during self-serving processes. Furthermore, we assume that insula activation is a correlate of awareness of personal agency in negative situations.
Gesehen am 28.01.2021